QUALITATIVE ANALYSIS OF PEOPLE EMOTION DRIVING CONSPICIOUS LUXURY CONSUMPTION AT BMW CONSUMER - Kattang, Fiorent E.C.; Tulung, Joy E.; Tielung, Maria V. J. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2021)
Emotion is basically a natural instinctive state of mind deriving from one's circumstances, mood, or relationships with others. If we try to distinguish the emotion felt when people do luxury purchase in this case BMW car there are not only one kind of emotion but several emotions felt in the process because to be able to purchase such meaningful transaction so many emotion pops up one after another that is why when people purchase luxury stuffs it takes longer time than the basic everyday purchase. The aim of this research is to know what emotion felt by the customer when they do luxury consumption of BMW car. To achieve these objectives, the researcher got information from 10 informants using qualitative study which is in-depth interview. Meanwhile, in-depth interview is used to collect the data among the respondents which are BMW consumer. From the results, many of the informant are having the same thought but as we human are not exactly the same one with another there are always little thing that difference them all but for the big picture they shown the same type of emotion. Some recommendations proposed for the customer, it is good to know about the emotion felt when purchasing luxury stuffs so those who will do the purchase in the future can be more considerate with their judgment. For BMW, this research may be useful to understand more on what people are expecting from their product and the thing that still need to be modified to improve BMW performance in people eyes and keep up the good image.Â Keywords: luxury consumption, consumer behaviour